Technical Report Series I - Chai, Elena Gregoria Chin Fern; Wang, Yin Chai; Lee, Jun Choi; Ngu, Sze Song; Siti Mariam, Abdullah; Florianna Lendai, Michael Mulok; Awang Ideris, Awang Daud (Unimas, 2019)
This research project is a collaboration between Universiti Malaysia Sarawak (UNIMAS), Sarawak Culture Research Institute Society and Association of the Boards of Management of Aided Chinese Primary Schools in Kuching, Samarahan and Serian Divisions. The study focuses on the coping strategies of non-Chinese students and families in Chinese primary schools in Sarawak.